2022
DOI: 10.31616/asj.2020.0566
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and the Development of Lumbar Canal Stenosis: Is There Any Relevance?

Abstract: Study Design: Retrospective study.Purpose: To assess the relationship between the severity of lumbar canal stenosis (LCS) and type-II diabetes mellitus (DM).Overview of Literature: DM is a multiorgan disorder that has an effect on all types of connective tissues. LCS is a narrowing of the spinal canal with nerve root impingement that causes neurological claudication and radiculopathy. Identification of the risk factors of LCS is key in the prevention of its onset or progression.Methods: LCS patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Regarding the impact of DM duration on the likelihood of LSS diagnosis, our findings align with other studies that suggest a correlation between prolonged exposure to DM and an early onset of DM diagnosis with an elevated risk of DM-related complications 21,24,25 In alignment with our findings, Iderberg et al 26 identified an association between various socioeconomic factors (such as country of birth, educational level, social welfare, and employment status) and the outcomes of LSS surgery 15 . In addition, our observation of a diminished likelihood of LSS in individuals with higher physical activity levels corresponds with prior research, suggesting that increased physical activity can improve pain and function in this population 27 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the impact of DM duration on the likelihood of LSS diagnosis, our findings align with other studies that suggest a correlation between prolonged exposure to DM and an early onset of DM diagnosis with an elevated risk of DM-related complications 21,24,25 In alignment with our findings, Iderberg et al 26 identified an association between various socioeconomic factors (such as country of birth, educational level, social welfare, and employment status) and the outcomes of LSS surgery 15 . In addition, our observation of a diminished likelihood of LSS in individuals with higher physical activity levels corresponds with prior research, suggesting that increased physical activity can improve pain and function in this population 27 .…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggested that DM may contribute to the pathogenesis of LSS. 9,10,21,22 In this large cohort study, we investigated the epidemiological connection between DM and LSS. We also conducted an analysis of additional risk factors for LSS and examined the mortality rates within the study populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the possible causes that can explain the association of spinal pain (NP and/or LBP) with diabetes are that people with diabetes have an increased risk of cartilage inflammation, loss of muscle strength, spinal stenosis, and degenerative intervertebral disc (IVD) disease [ 6 , 7 , 8 , 13 , 14 ]. The arguments for a spurious association between spinal pain and diabetes include the confounding effect of obesity, depression, and sedentarism, conditions more frequent among people with diabetes than without [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%